Porous lightweight composites reinforced with fibrous structures - Yang, Yiqi.; Yu, Jianyong; Xu, Helan; Sun, Baozhong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides a comprehensive coverage of raw materials, product design, processing technologies, performance properties, and current and prospective applications of diverse lightweight composites reinforced with fibrous structures. Contributed by internationally recognized experts in lightweight composites, for the first time, this book · focuses on composites reinforced with hollow organic fibers, such as feathers and straws, and inorganic fibers, such as hollow carbon fibers; · covers different technologies, such as 3D weaving, 3D braiding, and 3D knitting, for development of hollow fibrous structures as reinforcements; · provides an overview on technologies, such as foaming and supercritical drying, that induce pores or voids into matrices; · discusses specific applications of lightweight composites in areas such as biomedical engineering and automotive engineering.
High Performance Composites Produced from Dry-Processable Multi-Walled Carbon Nanotubes -- Composites Reinforced with Hollow Natural Organic Fibrous Structures -- Hollow/Porous Three-Dimensional Woven Structure Reinforced Composites -- Virtual Testing of Three-Dimensional Hollow/Porous Braided Composites -- Hollow Three-Dimensional Knitted Structure Reinforced Composites -- Advanced Grid Structures Reinforced Composites -- Porous Structures From Fibrous Proteins for Biomedical Applications -- Porous Structures from Biobased Synthetic Polymers via Freeze-Drying -- Porous Structures from Bio-Based Polymers via Supercritical Drying -- Carbon Nanotube-Based Aerogels as Preformed Porous Fibrous Network for Reinforcing Lightweight Composites -- Porous Lightweight Composites Reinforced with Natural and Agricultural Byproduct-Based Fibrous Structures -- Biobased Composites for Medical and Industrial Applications -- High-Performance Composites and Their Applications.
Keywords: Ceramic materials; Engineering; Manufactures; Ceramics; Technology and Engineering; Machines, Tools, Processes